(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article examines the features of poetry and style of the modern writer Plato colloquial. Using the method of comparative studies, the author analyzes this macaque and tries to reveal the peculiarities of the work of Russian writers of Uzbekistan.